2008
DOI: 10.1624/105812408x324534
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Posttraumatic Stress Symptoms After Childbirth: Does Ethnicity Have an Impact?

Abstract: The purpose of this descriptive, correlational study was to examine the prevalence of posttraumatic stress symptoms in mothers during the first 6 months after giving birth, as well as to investigate whether ethnicity has an impact on the occurrence of such symptoms. Twenty-two women completed the Perinatal Posttraumatic Stress Disorder (PTSD) Questionnaire at a community health center. Data analysis included descriptive statistics, correlations, and independent sample t-tests. Higher total Perinatal PTSD Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
1
12
0
2
Order By: Relevance
“…Thorough communication between staff and women during and after delivery should be encouraged [13,28,38]. Excellent pain management and opportunities for decision-making on the part of women could be presented to promote empowerment [10,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorough communication between staff and women during and after delivery should be encouraged [13,28,38]. Excellent pain management and opportunities for decision-making on the part of women could be presented to promote empowerment [10,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Also, ethnicity has been preliminarily examined. In one American study, an association between ethnicity and the avoidance symptom was found [28] while in another, no significant difference between ethnic groups (Caucasian, Asian and Pacific Islander) and prevalence of PTSD after childbirth was identified [29].…”
Section: Prevalencementioning
confidence: 94%
“…There are limited studies of PTSD among ethnically diverse perinatal populations. A study of the prevalence of PTSD in the Latina perinatal population did not obtain significant results due to an inadequate sample size (Paul, ). Another study by Onoye, Goebert, Morland, Matsu, and Wright (), evaluating changes in PTSD symptomatology and mental health during pregnancy and postpartum in the Asian and Pacific Islander populations did not obtain significant statistical results for similar reasons.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Specifically, the PTSD-Q, IES-R, PSS-SR, and TES were originally developed to measure posttraumatic stress symptoms following stressful events such as natural disasters, crime and traffic accidents. The PPQ is used to measure posttraumatic stress symptoms among women who gave birth to neonatal infants with complications [18][19][20]. Therefore, to accurately measure childbirth-related postnatal stress symptoms among women after birth, we should develop an appropriate scale.…”
Section: Introductionmentioning
confidence: 99%